2015
DOI: 10.15376/biores.10.1.1599-1616
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Surface and Paper Technical Properties of Eucalyptus globulus and Eucalyptus nitens Pulps after Modified Cooking and Bleaching

Abstract: The SuperBatch™(SB), CompactCooking™(CC), and Lo-Solids™ (LS) modified cooking methods were evaluated relative to the cell wall surface and paper technical properties of bleached Eucalyptus globulus and Eucalyptus nitens. E. globulus pulps presented higher screened yield and brightness than E. nitens, which needed higher H-factor to reach a kappa number target. Independently of the cooking method or species, all the samples consumed similar amounts of ClO2 to reach a brightness of 90% ISO. E. nitens pulps show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Additional bleaching steps and prolonged pulping in the bleached pulp grades 43 react first on the short chain-length polysaccharides in the wood i.e., the hemicelluloses. Higher amounts of hemicelluloses are correlated to higher water retention, 44 which is in good accordance to the different levels of water retention values for the pulps depicted in Figure 7.…”
Section: Swelling and Interdiffusionsupporting
confidence: 81%
“…Additional bleaching steps and prolonged pulping in the bleached pulp grades 43 react first on the short chain-length polysaccharides in the wood i.e., the hemicelluloses. Higher amounts of hemicelluloses are correlated to higher water retention, 44 which is in good accordance to the different levels of water retention values for the pulps depicted in Figure 7.…”
Section: Swelling and Interdiffusionsupporting
confidence: 81%
“…The Kappa numbers for B. spectabilis (35.66), F. altissima (31.33), and Ficus elastica (35.33) pulps were higher than those of E. globulus (17) [ 34 ], poplar cultivar ‘Hybrid 275’ (20.63) [ 20 ], E. camaldulensis (24), and M. sinclairii pulps (18) [ 30 ]. Additionally, the Kappa numbers recorded for Z. mays and S. bicolor pulps were comparable with that recorded for E. globulus pulp (17) [ 34 ] and lower than that for bamboo ( Gigantochloa scortechinii ) (14.2–18.1) [ 90 ]. Kraft pulping of bamboo chips was observed to produce a Kappa number of 17.4 [ 91 ], which is nearly comparable with our results for Z. mays (16.66) and S. bicolor (17.66).…”
Section: Resultsmentioning
confidence: 99%
“…A. nilotica wood was found to produce a significantly superior net pulp yield [ 29 , 30 ], and P. alba wood was shown to produce high-quality paper [ 29 ]. Furthermore, the small-diameter logs or branches resulting from the process of pruning fruit or timber trees have been studied in terms of their suitability for the production of pulp and paper [ 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The error bars present the standard deviation of the measurements. Antes and Joutsimo (2015c) An alternative explanation for the lower WRV could be related to the wall porosity of thicker fibers, which are more porous and cannot retain water by capillary action during the WRV measurement (Joutsimo 2004). Pulkkinen (2010) reported that larger fiber wall thickness resulted in lower water retention value (WRV).…”
Section: Cell Wall Porosity Measurements and Drainabilitymentioning
confidence: 99%